Sensory Evaluation of Pinked Sauvignon Blanc Wines - Nel, A.P.; du Toit, W.J.; van Jaarsvled, F.P. (South African Journal of Enology and Viticulture, 2021)
Sensorial studies on pinked white wines have never been carried out. The aim of this study was to establish the probability of an aroma and taste difference in pinked Sauvignon blanc wines using a triangular test. The issue of at which point a wine consumer can perceived the wine as pink was analysed using a ranking experiment. The probability that a wine taster can detect oxidised and pink wines as a wine fault was also analysed. It was found that the panellists could not detect anomaly samples by taste and aroma alone, although some noticed an oxidised aroma on the nose. The pink detection point was established at 0.03 AU. This point can be used to refine the detection point and the assay used. It was established that more than 50% of the panellists could detect oxidised and pink wines as a wine fault. The study data can be used to either train panellists to detect pinking as a wine fault, or to establish a potential new category for pink Sauvignon blanc wines.